Socratic Leaflet Education to Improve Couples’ Knowledge on Long-Term Contraceptive Selection - Hutabarat, Dewi Sartika; Tambun, Mastaida; Bakara, Srimuliana Putri; Butarbutar, Dyanti SR; Subroto, Edi; Aufa, Ka'sil (Asosiasi Dosen Muda Indonesia, 2026)
The high maternal mortality rate associated with frequent childbirth remains a significant public health issue, partly due to limited knowledge among couples of reproductive age about long-term contraception. The 2024 Indonesian Demographic and Health Survey reported that only 24.6% of respondents used long-term contraceptive methods. Low uptake is often linked to insufficient understanding and persistent myths in the community, indicating the need for interactive educational approaches. Objective: This study aims to analyze the effect of the Socratic method delivered through leaflets on improving the knowledge of couples of reproductive age in selecting Long-Term Contraceptive Methods (LTCM) at the Pematang Cengal Community Health Center. Methodology: The study employed a quantitative approach with a quasi-experimental one-group pre-test–post-test design. The population consisted of all couples of reproductive age within the health center’s service area, with 120 respondents selected through purposive sampling. Data were collected by measuring knowledge levels before and after the educational intervention and analyzed using the Wilcoxon Signed Rank Test. Findings: The results showed a statistically significant increase in the average knowledge scores after the Socratic-based education with leaflets (p-value < 0.05). Prior to the intervention, most respondents were categorized as having poor knowledge; afterward, the majority shifted to the good knowledge category. Implications: These findings suggest that interactive education using the Socratic method combined with leaflet media can serve as an effective strategy in primary healthcare settings to correct misconceptions, enhance understanding, and support informed decision-making regarding long-term contraception. Originality/Value: The originality of this study lies in the application of the Socratic method in LTCM education at the primary healthcare level, integrated with leaflet support, which promotes critical thinking about the effectiveness and safety of long-term contraception compared to conventional one-way education.